Money, a disconnecting agent: Reminders of money trigger a feeling of disconnection which increases the likelihood of unethical decisions. - Macdonald, Chris (Open Science Journal, 2019)
For eons many have hypothesized the corrupting influence of money, and yet, there has been a great void in the way of empirical experimentation. However, a series of pioneering experiments has begun to show confirmation of previous assumptions, one of which showed that the mere thought of money can loosen morals. This paper reveals three new experiments that explore the underlying process of this phenomenon. The results of experiments 1 and 2 suggest that individuals primed with money are less ethical than both a control group and individuals primed with business-related concepts. Further questioning revealed that an underlying mechanism behind the unethical decisions may be a decreased feeling of human connection. In accordance with this finding, the results of experiment 3 demonstrate that priming with disconnection themes directly results in a greater likelihood of unethical decisions.